Global positioning system (GPS) by Kalman filtering / Haris Sepikun - Sepikun, Haris (1998)
Thts thesis considers the imptementation of a Kalman Filter in a Global Positioning System (GPS) to improve its navigation performance. The GPS calculates the position (latitude and longitude) of any point on earth. The observable known as pseudorange is a timing measurement of the propagation delay that is due to the geometrie range from the transmitting satellite signal to the receiver ctock offset from satellite time. Kalman Filter is used to improve the navigation system which gives an accurate target tracking signal. This technique is used to process the pseudoranges and estimate the position and veiocity of the target tracking. Since the signals are non-linear, the tracker model used is the Extended Kalman Filter (EKF). The EKF approximates the optimum estimate by expanding non-linear system tunction into the Taylor-series about its normal operating values and, neglecting the high order term ie. by linearizing the nonlinear system.